The Impact of Non-Green Trade Openness on Environmental Degradation in Newly Industrialized Countries - van Hek, Sil; Can, Muhlis; Brusselaers, Jan (Ekonomikalia Journal of Economics, 2024)
Environmental degradation due to human over-exploitation is one of the most pressing global issues. The ten Newly Industrialized Countries (NICs) have recently witnessed substantial economic growth and involvement in global trade. In the discussion on environmental degradation, trade has a crucial role. Scholars use trade openness to test the scale effect on the environment. This research investigates the effect of non-green trade openness, economic growth, and energy consumption on ecological footprint. Panel estimation techniques such as cross-sectional dependence, slope homogeneity, unit root, and cointegration analyses are applied to panel data of ten NICs between 2003 and 2016. The Fully Modified Ordinary Least Squares (FMOLS) method reveals that non-green trade openness increases environmental degradation in the panel. Energy consumption and economic growth are also found to increase environmental degradation. Moreover, the Environmental Kuznets Curve (EKC) hypothesis is validated. The research presents a few relevant policy implications. The NICs should invest in green energy and an energy-efficient economy and focus on stimulating green trade as a catalyst for sustainable economic development in order to improve the quality of their environment. This can be done by introducing higher tariffs on non-green products and investing in technological innovations for green production methods and renewable energy. Although local environmental pollution in the European Union (EU) decreases, an increase in pollution in the NICs threatens the global state of the environment. Therefore, non-green trade should be approached as an international problem that has detrimental effects on all countries in different phases of economic development.